Duplication of leadership and management and the difference between them - Al-Omari, Rami Mahmoud Daifallah (Journal of Educational and Psychological Sciences, 2019)
Many of the concepts of management and leadership are mixed، and are thought to be meaningful. In fact، there is a big difference between the two concepts on more than one hand. The most important point of difference between management and leadership is what each focuses on. In the organization، excluding the human element، and vice versa in leadership، focusing heavily on the human element and interested in it and developing its skills، abilities and training to stimulate it to perform the work and achieve the goals. There is also a clear difference between the two parties. The leader is interested in influencing individuals based on his abilities and personal skills. The workforce feels that they are the focus of attention. He deals wisely and rationally with the involvement of the workers in the administrative process and avoids the use of delegated authority and official powers so as not to determine the form of the relationship Between him and his subordinates. The leader also keeps pace with changes in any current situation، always seeks continuous change، takes his subordinates' hand to the organization's progress and prosperity، encourages others to change and motivates them in their own way، and does not feel that there is a difference in job title. As for the manager، unlike the commander in all of the above، the manager resorted to forcing the subordinates to perform the functions and achieve the objectives of the organization based on a set of procedures and laws set by the senior management in the organization، and the relationship between him and his subordinates is very formal، lacking emotion and feelings given To neglect the human element of the Organization. The manager is not interested in making changes، but rather aims to achieve what the organization has devised without progress or noticeable growth in the performance of the organization and thus remain in its normal form. In addition، the manager is characterized by short-term planning، so he does not care about change but focuses all his thinking on time The current status of the organization and leave the future situation، and it is noted that the manager between him and his subordinates wide gap due to interest in the names of functional.
Keywords: management; leadership; organization; institution; manager; leader